Hackers and Hatewatchers: Tracing the origin stories of doxing - Theophilos, Jamie (AoIR Selected Papers of Internet Research, 2026)
Doxing—the unauthorized disclosure of private or personally identifying information online—has become one of the most contentious practices in contemporary digital culture. While often framed as a form of online harassment, doxing is also used as a tactic of accountability by antifascist groups and other online communities seeking to expose oppressive actors. This paper traces the early history of doxing from 1987 to 1999, exploring how the practice emerged across different online communities, including hacker forums, antifascist networks, and online vigilante groups. Drawing on archival materials, this study argues that doxing’s origins lie both in practices of deviance and subversion and in grassroots efforts to develop community safety. By situating doxing within alternative histories of the internet, this paper demonstrates how the weaponization of personal information has been shaped by both technological infrastructures and the social norms and politics of online subcultures. This intervention challenges dominant narratives that portray doxing solely as an act of malice, instead positioning it as one that is far more contested, revealing the internet’s dual capacity to enable both harm and community. Further, excavating the history of doxing offers an opportunity to analyze how the design, governance, and politics of the internet have shaped —and been shaped by— contentious and stigmatized practices.Together, this research highlights the ruptures between anonymity and accountability, spectacle and surveillance, information access and closure, and privacy and publicity that continue to shape the politics of online safety today.